(3hOGFY GdhUhd Edi Yde GdEUhds - (3GdbRhjfi, eMeO Hf GdMSf GdeOYh HegOi GdMSjfjs; (3YHO GdQMef Hf CMeO Hf YHO GdZaGQ, CHh GdaVd, nYoVO GdOjf GdEjLj,J (B756 (3g` s ((3eOjfI HZOGO OGQGdSdGe s)
(3ChdgG (B:s
(3hHYO ajbhd eMeO Hf GdMSf MjK Cf YHGQGJg ai GdQehR s
(3BNQgG (B:s
(3hHYO ajdRe CeG GdOhQ Ch GdJSdSd s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3CUhd Gdabgs